Profiles of Bullying in Schools: Analysis of Perpetrator, Victim, and Bystander Based on Demographic Factors - Maslihah, Sri; MIF Baihaqi; Hidayat, Ghinaya Ummul Mukminin; Mudin, Muhammad Ilham; Agestianti, Ruth (Psympathic : Jurnal Ilmiah Psikologi, 2025)
This study examines bullying profiles among perpetrators, victims, and bystanders in Bandung's junior and senior high schools, analyzing its relationships with demographic factors (gender, educational level, and age). A quantitative descriptive approach was used, with 1290 students ages 11-19 as participants. Data was collected using bullying instruments (perpetrator, victim, and bystander scales) developed by Maslihah et al. (2024), based on Salmivalli et al.'s (1996) bystander concept. Analysis included descriptive statistics, Spearman correlation, and independent t-test using SPSS 25. Results indicate bullying perpetrators constitute the smallest population group. Victim profiles showed no significant demographic differences. Significant differences in perpetrator roles emerged based on gender (p < 0.001), educational level (p < 0.001), and age (p < 0.001). Bystander roles varied, with several dimensions showing significant differences based on specific demographic factors. These findings provide an empirical basis for targeted interventions and responsive school policies addressing bullying.